Periodic solutions of impulsive systems with a small delay in the critical case of second order - Boichuk, A.A.; Covachev, V. (Нелінійні коливання, 1998)
We consider an impulsive differential-difference system such that the corresponding system without delay is linear and has an r-parametric family of w-periodic solutions. For this case, an equation for the generating amplitudes is derived, and sufficient conditions are obtained for the existence of wperiodic solutions of the initial system in the critical case of the second order if the delay is sufficiently small. Розглядається нелінійна періодична імпульсна диференціальна система із запізненням у припущенні, що відповідна система без запізнення є лінійною і має r -параметричну сім’ю періодичних розв’язків. Побудовано рівняння для породжуючих амплітуд такої задачі, що дає необхідну умову існування розв’язків. Одержані достатні умови існування періодичних розв’язків вихідної нелінійної системи у критичному випадку другого порядку при досить малому аргументу, що запізнюється.